Fate of atmospherically deposited NH4+ and NO3− in two temperate forests in China: temporal pattern and redistribution. Issue 6 (29th May 2019) - Li, Shanlong; Gurmesa, Geshere Abdisa; Zhu, Weixing; Gundersen, Per; Zhang, Shasha; Xi, Dan; Huang, Shaonan; Wang, Ang; Zhu, Feifei; Jiang, Yong; Zhu, Jiaojun; Fang, Yunting
Abstract: The impacts of anthropogenic nitrogen (N) deposition on forest ecosystems depend in large part on its fate. However, our understanding of the fates of different forms of deposited N as well as the redistribution over time within different ecosystems is limited. In this study, we used the 15 N‐tracer method to investigate both the short‐term (1 week to 3 months) and long‐term (1–3 yr) fates of deposited NH4 + or NO3 − by following the recovery of the 15 N in different ecosystem compartments in a larch plantation forest and a mixed forest located in northeastern China. The results showed similar total ecosystem retention for deposited NH4 + and NO3 −, but their distribution within the ecosystems (plants vs. soil) differed distinctly particularly in the short‐term, with higher 15 NO3 − recoveries in plants (while lower recoveries in organic layer) than found for 15 NH4 + . The different short‐term fate was likely related to the higher mobility of 15 NO3 − than 15 NH4 + in soils instead of plant uptake preferences for NO3 − over NH4 + . In the long‐term, differences between N forms became less prevalent but higher recoveries in trees (particularly in the larch forest) of 15 NO3 − than 15 NH4 + tracer persisted, suggesting that incoming NO3 − may contribute more to plant biomass increment and forest carbon sequestration than incoming NH4 + . Differences between the two forests in recoveries were largely driven by a higher 15 N recovery in the organic layer (both N forms) and in trees (for 15 NO3 − ) in the larch forest compared to the mixed forest. This was due to a more abundant organic layer and possibly higher tree N demand in the larch forest than in the mixed forest. Leachate 15 N loss was minor (<1% of the added 15 N) for both N forms and in both forests. Total 15 N recovery averaged 78% in the short‐term and decreased to 55% in the long‐term but with increasing amount of 15 N label (re)‐redistributed into slow turn‐over pools (e.g., trees and mineral soil). The different retention dynamics of deposited NH4 + and NO3 − may have implications in environmental policy related to the anthropogenic emissions of the two N forms.